Operasi Bisnis Transnasional dan Pembangunan Berkelanjutan: Eksplorasi Bibliometrik tentang Tanggung Jawab Sosial Perusahaan, Praktik Etis, dan Dampak Lingkungan - Na’afi, Septiana; Purwanti, Ari (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2023)
Achieving sustainable development in an era of transnational business operations requires a multidimensional understanding of the interactions between corporate practices, ethical considerations, and environmental impacts. This bibliometric analysis investigates the scholarly landscape of this multifaceted field, offering insights into key themes, influential works, and emerging trends. This study reveals a complex tapestry of research at the intersection of corporate social responsibility, ethical practices, and environmental sustainability by examining co-authorship networks, co-citation patterns, co-occurrence of keywords, and temporal shifts. Key publications, such as Elkington's triple bottom line framework and Mowforth and Munt's exploration of sustainable tourism, emerge as foundational pillars in the discourse. The analysis further highlights the importance of concepts such as sustainable growth, innovation, and the role of the private sector in driving sustainable development. As transnational corporations continue to shape the global economic landscape, this research provides essential foundations for informed decision-making and ongoing scientific inquiry for a sustainable future.